Vertical vibrations of a freight car as a uniaxial carriage from a wave of unevenness of the path - Djabbarov Shukhrat; Saidivaliev Shukhrat; Abdullaev Bakhrom; Inagamov Sardor; Abdusaid Yuldashov (E3S Web of Conferences, 2023)
The paper gives the results of mathematical modeling of movement of a loaded wagon with elastic suspension under viscous friction force equivalent to the dry friction force. Parameters of vertical relative forced vibrations have been found, which are stipulated by the wave of road irregularity.